Risk assessment on the shift to digital payments of SMEs in Tacloban City - Emberso, Liezel Mae C.; Ortiz, Jenine C.; Paete, Ma. Fiona Liana A.
The use of digital payments has grown rapidly in recent years. Existing studies and common belief posit that due to the immediate increase in use of digital payments, consumers and businesses alike delve into its use without enough knowledge on the risks upon its implementation and its effects thereafter. Consequently, some studies show that some businesses suffer due to the lack of awareness on how to deal with and mitigate these risks. Hence, with this study the researchers studied the SMEs operating within Tacloban City to assess their exposure and experiences on the inherent risk of digital payments and its effect on their business performance. The researchers did a physical survey among SMEs of Tacloban City. The data gathered were assessed quantitatively using Likert scales and correlational analyses. Results showed that, unlike existing literature and popular belief, most of the respondents already had prior knowledge on the risks of digital payments. However, these SMEs have only experienced minimal risks upon their use of digital payments, while data suggests that their business performance has been positively influenced by this new payment system. Further, results suggest that there is a negative moderate to strong correlation between experienced risk and business performance of SMEs. This suggests that there is an economic potential that could be maximized with digital payments with observed reduced risks and increased business performance.